(3TQM GdeQTOIs - (3YHO Gddg Hf HgGA GdOjf eMeO GdTfThQis; (3TgGH GdOjf CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,J (B815 (3g` s ((3UGdM Hf eMeO Hf Rjf GdYGHOjf s)
(3ChdgG (B:s
(3GdYOO GdCbd GdeWQhM chVY GdYOOjf GdeLehYjf ajeG JbOe s
(3BNQgG (B:s
(3ef dg ai JMUjd GdYdhe hdjaQZ ajg geg djahR HGdefWb efg hGdeaghe Ef TGA Gddg JYGdi hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HChdgG hbajI HGSe edG YHO Gddg GdYHOdi Ydi ChdGOg jQLY JGQjNgG Edi SfI (B1239 (3g`s
(3hQO ai cTa GdXfhf L(B2 (3U` (B1655 (3Cf eQTOI GdWGdH Edi CSfi GdeWGdH deDdaI GHf GdgGFe GdeJhai SfI (B815 (3g` s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdeLGejYs